PROFIT SHARING FINANCING FACTORS IN ISLAMIC BANKING - Hardi Fardiansyah; Nanda Dwi Rizkia; Irma Maria Dulame; Rahmawaty Arifiani (BADAN PENERBIT STIEPARI PRESS, 2023)
Sharia bank profit sharing financing is divided into mudharabah and musyarakah financing based on profit sharing or revenue sharing schemes. This scheme is very different from interest-based conventional bank credit. The aim of the study was to analyze the effect of third party funds (DPK), financing to deposit ratio (FDR), and non-performing financing (NPF) on financing for the results of Islamic banking in Indonesia. The study consisted of 35 observations covering the period August 2019 to August 2022. Data were analyzed using the multiple linear regression method. The research found that DPK and FDR had a positive effect on profit-sharing financing, while NPF had a negative effect on profit-sharing financing. The lower the bank's risk, the higher the collection of customer funds,